2013
DOI: 10.1016/j.biopsych.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Reward Learning Predicts Outcome in Major Depressive Disorder

Abstract: Background Reduced reward learning might contribute to the onset and maintenance of major depressive disorder (MDD). In particular, the inability to utilize rewards to guide behavior is hypothesized to be associated with anhedonia, a core feature and potential trait marker of MDD. Few studies have investigated whether reduced reward learning normalizes with treatment and/or reward learning predicts clinical outcome. Our goal was to test that MDD is characterized by reduced reward learning, especially in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
308
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(332 citation statements)
references
References 42 publications
(56 reference statements)
21
308
3
Order By: Relevance
“…In such tasks, HCs typically develop a reward response bias, learning to choose the stimulus associated with high-probability win and avoid the stimulus associated with high-probability loss in order to maximize payoffs. MDD patients fail to develop a reward response bias, resulting in reduced likelihood of choosing the stimulus associated with high-probability win [19][20][21]. The MDD group was found to be significantly less likely to choose the correct symbol in the win condition associated with highprobability win compared with the HC group at baseline in the present study, again consistent with previous research.…”
Section: (B) Reward Processingsupporting
confidence: 90%
See 1 more Smart Citation
“…In such tasks, HCs typically develop a reward response bias, learning to choose the stimulus associated with high-probability win and avoid the stimulus associated with high-probability loss in order to maximize payoffs. MDD patients fail to develop a reward response bias, resulting in reduced likelihood of choosing the stimulus associated with high-probability win [19][20][21]. The MDD group was found to be significantly less likely to choose the correct symbol in the win condition associated with highprobability win compared with the HC group at baseline in the present study, again consistent with previous research.…”
Section: (B) Reward Processingsupporting
confidence: 90%
“…Depressed patients display blunted responsiveness to reward [18] and fail to develop a response bias towards high-probability win during probabilistic instrumental learning tasks [19][20][21]. These impairments correlate specifically with the severity of self-reported anhedonia, independently of overall depression severity [21][22][23][24]. Building on pre-clinical evidence for a role of dopamine in reward [25,26], it has been hypothesized that the anhedonia and underlying impaired reward processing in depression involve changes in the function of the dopamine system.…”
Section: Introductionmentioning
confidence: 99%
“…The wealth of empirical studies strongly suggest that individuals with clinical and subclinical depression are impaired in their response to rewards both during the anticipatory (i.e., motivational) phase and during the consummatory (i.e., emotional) phase (for a detailed discussion about the distinction between these two phases, see Berridge and Robinson, 2003;Gard et al, 2006). Specifically, depressed individuals report less anticipated pleasure (e.g., Chentsova-Dutton and Hanley, 2010), show impaired reward-learning behavior (e.g., Huys et al, 2013;Liu et al, 2011;Vrieze et al, 2013), demonstrate impaired reward-related decision making (e.g., Kunisato et al, 2012;Treadway et al, 2012), have reduced activity in approach-related cortical regions (e.g., Shankman et al, 2013; for a review see Thibodeau et al, 2006), and show altered activity in reward-related brain regions (for a review see Zhang et al, 2013). Recently, we have shown reduced effort-related cardiovascular reactivity during goal pursuit in subclinical depression (Brinkmann and Franzen, 2013;Brinkmann et al, 2009;Brinkmann, 2015, 2016a).…”
Section: Reward Responsiveness In Depressionmentioning
confidence: 99%
“…In a series of studies, Pizzagalli and colleagues have investigated impairments in the ability, or propensity, to develop a response bias toward stimuli that are more frequently rewarded than others using a probabilistic reward task (Pizzagalli et al, 2005(Pizzagalli et al, , 2008Pechtel et al, 2013;Vrieze et al, 2013). The task has been applied to patients with varying degree of depressive and anhedonia symptoms and findings from these studies consistently show evidence of impaired reward learning.…”
Section: Impaired Ability To Learn About Rewardmentioning
confidence: 99%
“…In the first study, Pizzagalli et al (2005) showed that in participants with low levels of depressive symptoms there was an increase in the response bias over time, which was not present in participants with high levels of depressive symptoms. Subsequent studies of clinical populations show evidence of diminished reward responsiveness in depressed patients compared with controls (Pizzagalli et al, 2008;Vrieze et al, 2013), in patients with remitted depression compared with controls (Pechtel et al, 2013), and in depressed patients with high vs. low levels of anhedonia symptoms (Vrieze et al, 2013).…”
Section: Impaired Ability To Learn About Rewardmentioning
confidence: 99%